Human rights in India : theory and practice - Anand, Adarsh Sein, 1936-; Afonso, A. V.; Indian Institute of Advanced Study (Shimla : Indian Institute of Advanced Study, 2011)
Papers presented at a seminar jointly organized by Indian Institute of Advanced Study and National Human Rights Commission, New Delhi.
Includes bibliographical references
Keywords: Civil rights -- India; Human rights -- India